Coming unmoored: Disproportionate increases in obesity prevalence among young, disadvantaged white women. (8th October 2014) - Robinson, Whitney R.; Kershaw, Kiarri N.; Mezuk, Briana; Rafferty, Jane; Lee, Hedwig; Johnson‐Lawrence, Vicki; Seamans, Marissa J.; Jackson, James S.
<x xml:space="preserve">Abstract</x> Objectives Since the 1980s, older, low‐educated White women experienced an unprecedented decrease in life expectancy. We investigated whether a similar phenomenon was evident among younger women for obesity. Methods Using the National Health and Nutrition Examination Survey, age‐adjusted changes were estimated in the prevalence of overall and abdominal obesity (BMI ≥ 30 kg/m2, waist circumference > 88 cm) between 1988‐1994 and 2003‐2010 among non‐Hispanic White women aged 25‐44 years, stratified by educational attainment (<high school (HS), HS, some college, college degree). To address bias from secular increases in educational attainment, White women's changes in obesity prevalence were compared to changes among similarly educated Black women. Results Relative increases in overall obesity were disproportionately larger for low‐educated (<HS) compared to college‐educated White women: 12.3 (95% CI: 3.1, 21.5) percentage points (ppts). For overall and abdominal obesity, general trends indicated dissimilar racial differences by educational attainment. For instance, overall obesity increased more in Blacks than Whites among college‐educated (9.9 ppts) but not low‐educated (−2.5 ppts) women. Conclusions Contemporary young, low‐educated White women showed indications of disproportionate worsening of overall obesity prevalence compared to more educated White and similarly educated Black women. Low education levels are more powerful indicators of obesity risk among contemporary White women than 30 years ago.